2010
DOI: 10.1111/j.1365-2184.2010.00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Mouse sarcoma L1 cell line holoclones have a stemness signature

Abstract: Accumulating data suggest that cancers contain a fraction of cells called cancer stem cells (CSCs), that may be responsible for upkeep and relapses of disease. In experimental settings, CSCs are regarded as most effective at tumour initiation in in vivo assays. Since the first isolation of cancer stem cells from acute myeloid leukaemia in 1994, cancer stem cells have been identified in human solid tumours and they have also been found in the established cell lines, based on ability of CSCs to form in vitro col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…Also, the lowest efficiency of holoclone formation was found in MCF7-RFP cells. As The major characteristic of CSCs is to neutralize the effect of anticancer drugs via efflux transporter proteins (21,26). In this study, the holoclones of MCF7 and MDA-MB-231 cells showed resistance to Dox.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Also, the lowest efficiency of holoclone formation was found in MCF7-RFP cells. As The major characteristic of CSCs is to neutralize the effect of anticancer drugs via efflux transporter proteins (21,26). In this study, the holoclones of MCF7 and MDA-MB-231 cells showed resistance to Dox.…”
Section: Discussionmentioning
confidence: 70%
“…Multidrug resistance assay. Single-cell-derived holoclones were treated with Dox (1.5 μg/ml) for 24 h as reported (21). Control and treated clones were fixed as described and nuclei were stained with 4' 6-diamidino-2-phenylindole dihydrochloride (DAPI; 5 μg/ml) for 20 min in dark.…”
Section: Methodsmentioning
confidence: 99%
“…B16-F10 mouse melanoma (ATCC ® CRL-6475 ™ ) and L1 mouse sarcoma cells derived from a lung metastasis of a BALB/c mouse [ 20 ] were cultured in Dulbecco’s Modified Eagle Medium (Gibco BRL, Life Technologies) supplemented with 10% FBS (Lonza, BioWhittaker). Cells were maintained at 37°C in a humidified 5% CO 2 atmosphere with media changes every third day.…”
Section: Methodsmentioning
confidence: 99%
“…There were reports about the high intracellular GRP78 levels in CSC-like cells of different origins [206][207][208]212]. In 2010, Wu et al demonstrated that knockdown of GRP78 in tumor-initiating (CSC-like) cells from head and neck cancer impairs their self-renewing capacity, tumorigenic potential, and expression of stemness-related genes, while reducing the SP cell's proportion and enhancing apoptosis [213].…”
Section: Intracellular Grp78mentioning
confidence: 99%